Framing Gibran’s Vice Presidential Candidacy: A Gioia Model Analysis of Media Influence on Public Opinion in Political Communication - Alamsyah, Anggriani (CHANNEL: Jurnal Komunikasi, 2024)
This paper aims to explore how the media framing the candidacy of Gibran as vice president for Prabowo. The author uses the framing media proposed by Gioia which introduces three stages of inductive framing, namely theme determination, first-stage categorization, and second-stage categorization. Framing analysis, as developed by Gioia (1983), is a qualitative research method used in which an individual or group constructs meaning about a particular problem or phenomenon based on their individual experience. Framing analysis provides insight into how the media directs or influences the opinions of its audience through the selective presentation of information and interpretation of events. The result showed that online media framing can shape public opinion, which has contributed to the highest achievement for Prabowo-Gibran, despite all the controversies. This study contextualizes its results on political communication and framing analysis. Further research on another kind of framing is still needed in this subject